Effect of the reaction medium on the characteristics of silanized titanium dioxide particles: Differences obtained in the Zeta potential data and infrared spectra - E. Delgado Alvarado; L. López-Zamora; Cristina Pérez Pérez; E. Pérez; J.A. Vazquez-Lopez; J.A. González-Calderón (Data in Brief, 2018)
In this document we present the differences in the Zeta potential and in the Infrared spectra data obtained from the characterization of silanized titanium dioxide particles, using two different solvents as reaction media: ethanol and toluene. Also, we provide micrographs of transmission electron microscopy in order to show morphological differences between the analyzed samples.